MENINGKATKAN HASIL BELAJAR PASSING ATAS BOLA VOLI MELALUI PERMAINAN VOLSAL PADA SISWA KELAS V SD NEGERI CABLIKAN KECAMATAN REBAN KABUPATEN BATANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the increase in student learning outcomes in learning volsal passing up through the game in the fifth grade elementary school Cablikan Batang. The researchers plan a study using action research methods class. The design of classroom action research was conducted in two cycles with stages of planning, action, and reflection. The research subjects were students of class V Elementary School District Cablikan Reban Batang. Data collection techniques using the test methods, methods of documentation, and questionnaires. The results showed that through the game volsal, student learning outcomes first cycle indicates that 50% or 10 students achieve mastery learning and 50% or 10 students who have not achieved mastery learning, and student learning outcomes second cycle showed that 90% or 18 students achieve mastery study and 10% or 2 students who have not achieved mastery learning. Because classical completeness percentage of student learning outcomes beyond 80%, the study of this class action has achieved success indicators. Conclusions from this research is learning through play volsal can improve student learning outcomes fifth grade elementary school district Cablikan Reban Batang in the Academic Year 2012/2013.